1998
DOI: 10.1108/eb022526
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction in the clothing market

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even though there are studies on satisfaction in ready-made clothing (Shim and Bickle, 1993;Wehfritz et al, 1998), there are few studies on the relationship between satisfaction and repurchase intention. In their study conducted with 233 consumers purchasing fashion products, Cui and Niu (2017), found that dissatisfaction has a negative effect on repurchase intention.…”
Section: Relationship Between Dissatisfaction and Repurchase Intentionmentioning
confidence: 99%
“…Even though there are studies on satisfaction in ready-made clothing (Shim and Bickle, 1993;Wehfritz et al, 1998), there are few studies on the relationship between satisfaction and repurchase intention. In their study conducted with 233 consumers purchasing fashion products, Cui and Niu (2017), found that dissatisfaction has a negative effect on repurchase intention.…”
Section: Relationship Between Dissatisfaction and Repurchase Intentionmentioning
confidence: 99%
“…Researches on consumers’ satisfaction of various products have been looked into in the past with a view to measuring how satisfied consumers of such products are. These researches range from satisfaction on food (Espejel et al, 2008; Suchánek & Králová, 2019), housing (Puķīte & Geipele, 2017; Suffian et al, 2016), clothing (Nonaka et al, 2014; Wehfritz et al, 1998), transportation (Amponsah & Adams, 2016; Margareta & Markus, 2009) and electricity (Drosos et al, 2020; Souza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%